The tooth fairy - Jones, Janey Louise (London : Picture Corgi books, 2010)
Poppy is desperate for the tooth fairy to visit her but there's just one problem ...none of her teeth are even wobbly yet. All her friends have had a visit from the tooth fairy and Mimosa even says she's seen her. Poppy feels very left out indeed and is worried that her time will never come.
K-3.
Keywords: Tooth Fairy -- Fiction; Princess -- Fiction; Teeth -- Fiction